Implementation of Disciplinary Character Education: A Comparative Study of Indonesian and Australian Elementary School - Azzahra, Azizah; Hidayat, Muhamad Taufik (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: The research aims to compare the implementation of disciplinary character education in Indonesia and Australia. Methodology: This research adopts a qualitative approach employing the Study Literature Review method within the Comparative Literature Review research framework. The data corpus comprises journal articles, online resources, and scholarly books. The data collection methodology commences with an extensive literature review, followed by meticulous data categorisation and selection based on identifying pertinent disciplinary elements. The validity of the data is ensured through rigorous reader persistence, corroborative validation from established scholars, and triangulation of sources. Data analysis encompasses data reduction, presentation, and inference techniques to draw comprehensive conclusions. Results: The research findings reveal similarities and disparities in implementing disciplinary character education between Indonesia and Australia. The congruences observed include (1) The delineation of school regulations aimed at cultivating a disciplined ethos among all school community members. (2) Providing awards to students as a mechanism to reinforce compliant behaviour and foster a sense of accountability. (3) The utilisation of punitive measures to serve as a deterrent for students who transgress the established norms. (4) Consistent efforts towards inculcating discipline, such as adherence to punctuality. Conversely, notable distinctions emerge, notably in the formulation of school regulations. In Indonesia, these regulations are typically crafted by teachers and school principals. Conversely, within the public school system in Australia, teachers are vested with the authority to enforce disciplinary measures as delineated by the 2019 Education and Children’s Services Act. Applications/Originality/Value: This research compares disciplinary character education in Indonesia and Australia.